The biology of soil : a community and ecosystem approach. - Bardgett, Richard D., ....- (New York : University Press, 2005)
Preface and acknowledgements; The soil environment; The diversity of life in soil; Organism interactions and soil processes; Linkages between plant and soil biological communities; Above-ground trophic interactions and soil biological communities; Soil biological properties and global change; Conclusions; Bibliography; Index
Keywords: Bodemkunde